Dream recall, nightmare frequency, and spirituality - Schredl, Michael; Stumbrys, Tadas; Erlacher, Daniel (Dreaming, 2016)
Dreaming plays a role in all major world religions, so it was expected that dream recall frequency was positively related to a measure of spirituality ('Transpersonal Trust'). The findings of the online survey (N = 528) indicate that there is a relationship between spirituality and dream recall, possibly mediated by mindfulness skills. Two factors might explain this relationship: First, dreams can provide spiritual inspiration and, second, spiritual practices like meditation can increase dream recall. Interestingly, mindfulness was related to lower nightmare frequencies. It would be very interesting to study dreaming in persons undergoing intense spiritual training with regard to, on the one hand, possible beneficial effects of spiritual dreams and, on the other hand, the effect of the spiritual training on dream content.
Gesehen am 14.03.2019